STRATEGI DAN MOTIVASI BELAJAR ANAK USIA DINI DI TK CENDIKIA RINJANI MANDIRI DI DUSUN LENDANG BILE DESA BUNUT BAOK - Riana Hastuti (Golden Age and Inclusive Education, 2024)
The purpose of this research is to determine teacher motivation and obstacles in increasing the motivation of young children. To explore this, the researcher used qualitative research with methods and data analysis using reduction, presentation, and conclusion. The results of this research show that: (1) Teacher strategies in increasing the learning motivation of young children at Cendikia Rinjani Mandiri Kindergarten include direct learning strategies, indirect learning strategies, and interactive learning strategies. The increase in learning motivation for early childhood at Cendikia Rinjani Mandiri Kindergarten is quite good, with learning strategies and methods with intrinsic and extrinsic motivation.